Polarization-Insensitive Electro-Absorption Modulator Based on Graphene-Silicon Nitride Hybrid Waveguide - Wei Chen; Xiaojian Fan; Pengfei Li; Yang Gao; Lanting Ji; Xiaoqiang Sun; Daming Zhang (IEEE Photonics Journal)
Wideband and polarization-insensitive operation are key issues for electro-optic modulators. An electro-absorption modulator based on graphene-silicon nitride hybrid waveguide has been proposed. Geometric parameters are investigated through finite element method to enhance the interaction between the optical mode and the graphene. For a 200-µm-long hybrid waveguide, a modulation depth (MD) of 20 dB can be obtained when Femi level varies from 0.2 to 0.6 eV. The MD difference between the transversal electric polarization and transversal magnetic polarization (ΔMD) can be restrained to 4 × 10−3 dB at 1550 nm. A low average ΔMD of 0.2 dB within the wavelength range from 1100 to 1645 nm can be obtained. The 3 dB-bandwidth of 53 GHz and a power consumption is 0.687 pJ/bit can be obtained. The proposed modulator has potentials for on-chip signal processing.